If it's not what You are looking for type in the equation solver your own equation and let us solve it.
10=3x+7(x-10)
We move all terms to the left:
10-(3x+7(x-10))=0
We calculate terms in parentheses: -(3x+7(x-10)), so:We get rid of parentheses
3x+7(x-10)
We multiply parentheses
3x+7x-70
We add all the numbers together, and all the variables
10x-70
Back to the equation:
-(10x-70)
-10x+70+10=0
We add all the numbers together, and all the variables
-10x+80=0
We move all terms containing x to the left, all other terms to the right
-10x=-80
x=-80/-10
x=+8
| -24-8x=12 | | x-57=43 | | 11=6k=65 | | 3w=-15-6 | | 2x^2+11=9x | | 10=3x+4(4x+20) | | 7p-3=5p=1 | | 5-13=k | | 6+8n=24 | | 5x+121.175=-246.875 | | 4x+3(3x-17)=92 | | 3X+5(4x+15)=190 | | 100+h^2=467 | | 4x+5(6x-21)=235 | | 5w+12=112 | | (6)10=128x | | 3w2–16w+16=0 | | (6)(10)=128x | | b+5/6=25 | | 6•10=128x | | 5c+5=23 | | 142/3n=3/5 | | 6x10=128x | | 32=0.4x | | 5x+2(5x-21)=33 | | 10x-(3x+30)=40 | | 8-4m=m+13 | | 2t=13-3t | | 4=k-(-12) | | 12+w=74 | | 144=6x+3(4x+12) | | 6(3y-4)-22=3(4y-5)-15 |